The Influence of Deposition Temperature on the Microscopic Process of Diamond-like Carbon (DLC) Film Deposition on a 2024 Aluminum Alloy Surface - Li Yang; Tong Li; Baihui Shang; Lili Guo; Tong Zhang; Weina Han (Crystals)
In this experiment, plasma-enhanced chemical vapor deposition technology was used to deposit diamond-like carbon thin films on the surface of a 2024 aluminum alloy. The effects of deposition temperature on the microstructure, carbon, silicon, and aluminum element distribution, and film substrate adhesion of diamond-like carbon thin films were studied using field emission scanning electron microscopy, energy-dispersive spectroscopy, XRD, scratch gauge, and ultra-depth-of-field microscopy. The results showed that with the increase in deposition temperature, the thickness of DLC film decreased from 8.72 μm to 5.37 μm, and the film bonded well with the substrate. There is a clear transition layer containing silicon elements between the DLC film and the aluminum alloy substrate. The transition layer is a solid solution formed by aluminum and silicon elements, which increases the bonding strength between the film and substrate. C-Si and C-C exist in the form of covalent bonds and undergo orbital hybridization, making the DLC film more stable. When the deposition temperature exceeds the aging temperature of a 2024 aluminum alloy, it will affect the properties of the aluminum alloy substrate. Therefore, the deposition temperature should be below the aging temperature of the 2024 aluminum alloy for coating. At a deposition temperature of 100 °C, the maximum membrane substrate bonding force is 14.45 N. When a continuous sound signal appears and the friction coefficient is the same as that of the substrate, the film is completely damaged. From the super-depth map of the scratch morphology, it can be seen that, at a deposition temperature of 100 °C, a small amount of thin film detachment appears around the scratch.